Innate Lymphoid Cells and Myocardial Infarction - Wenling Yang (Frontiers Media S.A., 2021)
Myocardial infarction results from obstruction of a coronary artery that causes insufficient blood supply to the myocardium and leads to ischemic necrosis. It is one of the most common diseases threatening human health and is characterized by high morbidity and mortality. Atherosclerosis is the pathological basis of myocardial infarction, and its pathogenesis has not been fully elucidated. Innate lymphoid cells (ILCs) are an important part of the human immune system and participate in many processes, including inflammation, metabolism and tissue remodeling, and play an important role in atherosclerosis. However, their specific roles in myocardial infarction are unclear. This review describes the current understanding of the relationship between innate lymphoid cells and myocardial infarction during the acute phase of myocardial infarction, myocardial ischemia-reperfusion injury, and heart repair and regeneration following myocardial infarction. We suggest that this review may provide new potential intervention targets and ideas for treatment and prevention of myocardial infarction.